Progression of Decomposed Local-Effect Action Theories - Ponomaryov, Denis; Soutchanski, Mikhail (ACM transactions on computational logic, 2017)
In many tasks related to reasoning about consequences of a logical theory, it is desirable to decompose the theory into a number of weakly related or independent components. However, a theory may represent knowledge that is subject to change, as a result of executing actions that have effects on some of the initial properties mentioned in the theory. Having once computed a decomposition of a theory, it is advantageous to know whether a decomposition has to be computed again in the newly changed theory (obtained from taking into account changes resulting from execution of an action). In this article, we address this problem in the scope of the situation calculus, where a change of an initial theory is related to the notion of progression. Progression provides a form of forward reasoning; it relies on forgetting values of those properties, which are subject to change, and computing new values for them. We consider decomposability and inseparability, two component properties known from the literature, and contribute by studying the conditions (1) when these properties are preserved and (2) when they are lost wrt progression and the related operation of forgetting. To show the latter, we demonstrate the boundaries using a number of negative examples. To show the former, we identify cases when these properties are preserved under forgetting and progression of initial theories in local-effect basic action theories of the situation calculus. Our article contributes to bridging two different communities in knowledge representation, namely, research on modularity and research on reasoning about actions.